Digital health at Central Lisbon University Hospital Center: Strategic reflections and value proposition - Varela, M.; Ferreira, F.; Ferreira, N.; Correia, R. (International Transactions of Operations Research, 2025)
Digital health emerges in the context of technological advancement, responding to the challenges of healthcare systems based on safe, quality healthcare services, offered in a timely manner, and in an efficient and effective way. However, digital health also brings challenges that are essentially related to change management within organizations. Based on problem structuring methods, this study sought to investigate the digital health topic in the specific case of Central Lisbon University Hospital Center (CHULC in Portuguese), aiming to reflect on initiatives that enhance digital health benefits within this organization and that contribute to its digital transformation. For this purpose, interpretive structural modeling was used to identify and understand the cause–effect relationships between determinants of digital health in this context, involving CHULC in the strategic reflection on the subject through a collaborative and constructivist approach. The main results include a set of actions formalized to enhance the center's digital health value proposition.